Metabolic Syndromes and Cardiovascular Disease: What is on the horizon? - Santoso, Anwar (Universitas Brawijaya, 2023)
Metabolic syndrome (MetS) is characterised by the simultaneous occurrence of at least three out of fivecardio-metabolic disorders.1, 2 These problems consist of visceral obesity, hypertension, high blood glucose, hightriglyceride, and low HDL cholesterol levels.2 It is unclear to what extent communities with diverse ethnicbackgrounds differ in the contributing factors. Additionally, the risk of cardio-vascular disease (CVD) mortalitymay vary depending on the frequency of MetS and its components in various ethnic groups and nations.3 Inappropriately,information on the CVD mortality risk associated with MetS is still quite limited, especially in Asiancountries. The majority of investigations were limited to determining the prevalence of MetS and its contributingvariables among Asians. Due mostly to unhealthy lifestyle such as an imbalanced diet high in carbohydrate andsedentary habits, the prevalence of MetS has been rising along with urbanisation.4